STUDY KOMPARATIF PROSEDUR PEMBERIAN KREDIT PEMILIKAN RUMAH PADA BANK SYARIAH DALAM HAL INI BANK MUAMALAT INDONESIA DENGAN BANK KONVENSIONAL DALAM HAL INI BANK TABUNGAN NEGARA - Anis Nur Nadhiroh (LPPM Universitas Bina Bangsa, 2022)
This research will be more directed at the installment process in providing mortgages to Conventional Banks, in this case Bank BTN and KPRS financing at Islamic banks, in this case bank Muamalat Indonesia. The method used in this study is normative. The results of this study explain that there are not too many differences in the provision of mortgages between the two banks, but there are the most striking differences in technical terms such as bank treatment of customers who are late in paying installments, and bank treatment of customers who want to pay off installments before their maturity, credit provision, contracts, relationships with customers, and installment calculations. Then the similarity between Islamic banks and the Convention is in the mortgage financing system which is in the process of applying for credit, procedures, sources of interest or profit margins and credit provision